IDENTIFIKASI MISKONSEPSI SISWA PADA KONSEP FOTOSINTESIS DAN RESPIRASI TUMBUHAN - Kartika Fandiyani; Tri Jalmo; Rini Rita T. Marpaung (Universitas Lampung, 2017)
This research aim was to describe students' misconception in the concept of plants photosynthesis and respiration and all factors that affected students' misconception. This research used descriptive design. The Samples were 351 SMP students of VIII grade at Tumijajar district academic year 2015/2016 which were chosen by using purposive sampling technique. Data were collected by multiple choicetest and student questionnaire. The test result were analyzed using the CRI, while the student questionnaire were analyzed using Pearson correlation test. The result of data analysis showed that students get misconception that was 57,30% with